Utilization of oil palm waste for the production of blockboard and compost and their environmental impact: a review / Zairul Azrin Md Zainordin - Md Zainordin, Zairul Azrin (Faculty of Plantation and Agrotechnology, 2016)
In Malaysia, palm oil industry is the most important commodity of this country and become the world's second-largest producer after Indonesia. Elaesis guneensis Jacq is one of the most productive oil palm in the world, which can produced 20 to 45 tons of fresh fruit bunch (FFB) in one hectare after 3 years planting (Singh, 2010). With this amount, it's produced high amounts of high value waste that can be utilized. One of the alternatives is the production of "block board" to reconcile the future demand of the low end furniture from the oil palm trunk. While in agricultural sector, it has proven that the oil palm frond have high potential to be composted to replace the peat moss as the humus amended with the soilless medium of the cauliflower crop. Therefore, in this review paper, we will discuss about the environmental impact when utilized the oil palm waste.